The expression of RUNX3 in colorectal cancer is associated with disease stage and patient outcome - Soong, R.; Shah, N.; Peh, B.; Chong, P.; Ng, S.; Zeps, Nikolajs; Joseph, D.; Salto-Tellez, M.; Iacopetta, B.; Ito, Y. (Nature Publishing Group, 2009)
RUNX3 is believed to have tumour suppressor properties in several cancer types. Inactivation of RUNX3 has been shown to occur by methylation-induced transcriptional silencing and by mislocalization of the protein to the cytoplasm. The aim of this study was to examine the clinical significance of RUNX3 expression in a large series of colorectal cancers using immunohistochemistry and tissue arrays. With advancing tumour stage, expression of RUNX3 in the nucleus decreased, whereas expression restricted to the cytoplasmic compartment increased. Nuclear RUNX3 expression was associated with significantly better patient survival compared to tumours in which the expression of RUNX3 was restricted to the cytoplasm (P=0.025). These results support a role for RUNX3 as a tumour suppressor in colorectal cancer. © 2009 Cancer Research UK.